Stable Isotopes from Museum Specimens May Provide Evidence of Long-Term Change in the Trophic Ecology of a Migratory Aerial Insectivore - English, Philina A.; Green, David J.; Nocera, Joseph J. (Frontiers in Ecology and Evolution, 2018)
Identifying the mechanisms of ecological change is challenging in the absence of long-term data, but stable isotope ratios of museum specimen tissues may provide a record of diet and habitat change through time. Aerial insectivores are experiencing the steepest population declines of any avian guild in North America and one hypothesis for these population declines is a reduction in the availability of prey. If reduced prey availability is due to an overall reduction in insect abundance, we might also expect populations of higher trophic level insects to have declined most quickly due to their greater sensitivity to a variety of disturbance types. Because nitrogen isotope ratios (delta 15N) tend to increase with trophic-level, while delta 13C generally increases with agricultural intensification, we used delta 15N and 13C values of bird tissues grown in winter (claw) and during breeding (feathers) from museum specimens spanning 1880–2005, and contemporary samples from breeding birds (2011–2013) to test for diet change in a migratory nocturnal aerial insectivore, Eastern Whip-poor-will (Antrostomus vociferus) breeding in Ontario, Canada. To test if environmental baselines have changed as a result of synthetic N fertilizer use, habitat conversion or climate, we also sampled delta 15N values of three potential prey species collected from across the same geographic region and time period. Over the past 100 years, we found a significant decline in delta 15N in tissues grown on both the breeding and wintering grounds. Prey species did not show a corresponding temporal trend in delta 15N values, but our power to detect such a trend was limited due to higher sample variance. Amongst contemporary bird samples, delta 15N values did not vary with sex or breeding site, but nestlings had lower values than adults. These results are consistent with the hypothesis that aerial insectivore populations are declining due to changes in abundance of higher trophic-level prey, but we caution that museum-based stable isotope studies of terrestrial food chains will require new approaches to assessing baseline change. Once addressed, an ability to decode the historical record locked inside museum collections could enhance our understanding of ecological change and inform conservation decisions.